Coming early to the party - Mario Bellia; Loriana Pelizzon; Marti Subrahmanyam; Jun Uno; Darya Yuferova (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
We examine the strategic behavior of High Frequency Traders (HFTs) during the pre-opening phase and the opening auction of the NYSE-Euronext Paris exchange. HFTs actively participate, and profitably extract information from the order flow. They also post "flash crash" orders, to gain time priority. They make profits on their last-second orders; however, so do others, suggesting that there is no speed advantage. HFTs lead price discovery, and neither harm nor improve liquidity. They "come early to the party", and enjoy it (make profits); however, they also help others enjoy the party (improve market quality) and do not have privileges (their speed advantage is not crucial).
urn:nbn:de:hebis:30:3-438747
Keywords: G12; G14; 330; High-Frequency Traders (HFTs); Proprietary Trading; Opening Auction; Liquidity Provision; Price Discovery